Parcerias e redes de relacionamento: um estudo de caso de uma organização não governamental - Stefani, Maria Teresa (2013)
Partnerships are instruments used by government entities and non-governmental organizations to expand the supply of services of public interest in the areas of health, education and social work, among others. In addition to those agreements, nonprofit-organizations develop other partnerships with different sectors of society, individuals and institutions that support improving the social reality of poor communities. Thus, this paper aims to discuss the partnerships that a nongovernmental organization establishes with governmental entities, where financial transfers are involved, with other governmental and private entities, where exchange of services or financial transfers is sporadic and limited to specific projects. The set of partnerships ultimately generates a network of relationships that changes with time. Therefore, the author developed a quantitative and qualitative case study of ARCO Associação Beneficente, a nongovernmental organization, whose service is intended for children and adolescents in the areas of education and social assistance. Three major perspectives of ARCO are evaluated: (i) its financial strength over the past 10 years, the partnership with the city government through agreements and projects sponsored by the Municipal Fund for Children and Adolescents, (ii) its relationship with the surrounding community where it is based, one of the poorest areas of the city of São Paulo, and (iii) the network of partnerships formed by ARCO along its 22 years of activity in the neighborhood. It was identified a jump in quality and quantity in services offered to the public attended, which has been held without interruption, although it generated to the entity a high level of financial dependence on resources provided by the City of São Paulo. Regarding the community, there is a high degree of social exclusion and most of the residents live in squalid conditions, with little prospects of a promising change in their current situation. There also is a great interaction with ARCO, who became a channel to their claims for seeking human rights and improve their conditions. It was also found that the established network is flexible and dynamic. Although not yet fully consolidated, it yet brings positive results in the supply of services for the community, which ultimately go beyond partnerships with governments. Finally, it was also found that the relationship with government officials is not as mutual as it could be, and that communication s noise hinders trust creation